A Randomized Crossover Trial Comparing Autotitrating and Continuous Positive Airway Pressure in Subjects With Symptoms of Aerophagia: Effects on Compliance and Subjective Symptoms - Shirlaw, Teresa (J Clin Sleep Med, 2017)
STUDY OBJECTIVES: To assess the benefit and tolerance of autotitrating positive airway pressure (APAP) versus continuous positive airway pressure (CPAP) in subjects who experience aerophagia. METHODS: This is the report of a prospective, two-week, double-blinded, randomized crossover trial set in an Australian clinical sleep laboratory in a tertiary hospital. Fifty-six subjects who reported symptoms of aerophagia that they attributed to CPAP were recruited. Full face masks were used by 39 of the 56 subjects recruited. Subjects were randomly and blindly allocated to either CPAP at their treatment recommended pressure or APAP 6–20 cm H(2)O, in random order. Subjects spent two weeks on each therapy mode. Therapy usage hours, 95th centile pressure, maximum pressure, 95th centile leak, and residual apnea-hypopnea index (AHI) were reported at the end of each two-week treatment period. Functional Outcome of Sleepiness Questionnaire, Epworth Sleepiness Scale, and visual analog scale to measure symptoms of aerophagia were also completed at the end of each 2-week treatment arm. RESULTS: The median pressure (P < .001) and 95th centile pressure (P < .001) were reduced with APAP but no differences in compliance (P = .120) and residual AHI were observed. APAP reduced the symptoms of bloating (P = .011), worst episode of bloating (P = .040), flatulence (P = .010), and belching (P = .001) compared to CPAP. There were no differences in Epworth Sleepiness Scale or Functional Outcome of Sleepiness Questionnaire outcomes between CPAP and APAP. CONCLUSIONS: APAP therapy reduces the symptoms of aerophagia while not affecting compliance when compared with CPAP therapy. CLINICAL TRIAL REGISTRATION: Australian and New Zealand Clinical Trials Registry at https://www.anzctr.org.au, trial number ACTRN12611001250921. COMMENTARY: A commentary on this article appears in this issue on page 859. CITATION: Shirlaw T, Hanssen K, Duce B, Hukins C. A randomized crossover trial comparing autotitrating and continuous positive airway pressure in subjects with symptoms of aerophagia: effects on compliance and subjective symptoms. J Clin Sleep Med. 2017;13(7):881–888.